Pirfenidone reduces subchondral bone loss and fibrosis after murine knee cartilage injury. Issue 1 (21st July 2017) - Chan, Deva D.; Li, Jun; Luo, Wei; Predescu, Dan N.; Cole, Brian J.; Plaas, Anna
ABSTRACT: Pirfenidone is an anti‐inflammatory and anti‐fibrotic drug that has shown efficacy in lung and kidney fibrosis. Because inflammation and fibrosis have been linked to the progression of osteoarthritis, we investigated the effects of oral Pirfenidone in a mouse model of cartilage injury, which results in chronic inflammation and joint‐wide fibrosis in mice that lack hyaluronan synthase 1 (Has1 −/− ) in comparison to wild‐type. Femoral cartilage was surgically injured in wild‐type and Has1 −/− mice, and Pirfenidone was administered in food starting after 3 days. At 4 weeks, Pirfenidone reduced the appearance, on micro‐computed tomography, of pitting in subchondral bone at, and cortical bone surrounding, the site of cartilage injury. This corresponded with a reduction in fibrotic tissue deposits as observed with gross joint surface photography. Pirfenidone resulted in significant recovery of trabecular bone parameters affected by joint injury in Has1 −/− mice, although the effect in wild‐type was less pronounced. Pirfenidone also increased Safranin‐O staining of growth plate cartilage after cartilage injury and sham operation in both genotypes. Taken together with the expression of selected extracellular matrix, inflammation, and fibrosis genes, these results indicate that Pirfenidone may confer chondrogenic and bone‐protective effects, although the well‐known anti‐fibrotic effects of Pirfenidone may occur earlier in the wound‐healing response than the time point examined in this study. Further investigations to identify the specific cell populations in the joint and signaling pathways that are responsive to Pirfenidone are warranted, as Pirfenidone and other anti‐fibrotic drugs may encourage tissue repair and prevent progression of post‐traumatic osteoarthritis. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:365–376, 2018. Abstract : Pirfenidone (PFD)—an anti‐inflammatory, anti‐fibrotic drug—has shown efficacy in lung and kidney fibrosis, while synovial inflammation and joint fibrosis are hallmarks of osteoarthritis progression. In a cartilage injury model in wild‐type and hyaluronan synthase 1 null mice, orally administered Pirfenidone, started at 3 days after injury, conferred joint‐protective effects. Pirfenidone reduced appearance of fibrotic tissue deposition on the joint surface after 4 weeks post‐injury. Micro‐computed tomography showed that Pirfenidone also reduced the loss of cortical, subchondral, and trabecular bone.